(The Formulation of Alginate and Pectin as Edible Coating For Salacca Fruit (Salacca edulis) Ready-to-Service) - M Maman Rohaman; Dheni M. Mala; Dwi Sutrisniati (Balai Besar Industri Agro, 2006)
The objective of the study was to develop and assess an edible coating from alginate and pectin that applied to sallaca ready service.The properties assess of sallaca ready-to-serve using edible coating consist of water content,total acid,vit.C,total glucosa,hardness,weight loss,TPC and browning.The chosen formulas were alginate 5%,pectin 5% and mixing between alginate and pectin.The best formula for sallaca ready-to-serve is pectin plus alginate 5% and stearic acid 0,25% it showed by the value of water activity(0,554)elongation percentage (53.33)tensile strength (122.744 kg.f) and water vapor transmition rate (484.41 g/persegi/24 hour).The physic and chemist property assays can be concluted that edible coating application with storage temperature 5 degree C could exted minimally processed salacca shelf life for 10 days.